1995
DOI: 10.1007/bf02109357
|View full text |Cite
|
Sign up to set email alerts
|

Manganese toxicity, dopaminergic dysfunction and hepatic encephalopathy

Abstract: Patients with chronic liver disease manifest a high incidence (> 75%) of pallidal signal hyperintensity on T1-weighted Magnetic Resonance Imaging (MRI), the intensity of which correlates with blood manganese levels and the presence of extrapyramidal symptoms. A major cause of pallidal hyperintensity on T1-weighted MRI is manganese deposition; chronic manganese intoxication in the absence of liver disease results in pallidal MR signal hyperintensity, in extrapyramidal symptoms and in selective effects on the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(95 citation statements)
references
References 32 publications
5
85
0
3
Order By: Relevance
“…Previous studies [6][7][8]22) have shown that subjective MR imaging scores correlated with blood Mn concentrations. The present study confirmed and extended previous reports showing a correlation between increased pallidal signals and blood Mn concentrations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies [6][7][8]22) have shown that subjective MR imaging scores correlated with blood Mn concentrations. The present study confirmed and extended previous reports showing a correlation between increased pallidal signals and blood Mn concentrations.…”
Section: Discussionmentioning
confidence: 90%
“…A similar MRI pattern has been observed in patients receiving total parenteral nutrition, because of excessive Mn intake 4,5) . Chronic liver failure is also associated with increased signal intensities in the GP using T1-weighted MRI 6,7) . The correlation between the MRI abnormalities in the GP and circulating Mn concentrations of cirrhotic patients suggests that the high signals are due to the paramagnetic Mn [8][9][10] .…”
mentioning
confidence: 99%
“…Chronic exposure to manganese devastates the central nervous system with symptoms strikingly similar to schizophrenia and Parkinsonism [1,2]. Brain lesions, marked by neuronal degeneration [3], are focal within brain regions that are particularly active in oxidative metabolism and have a significant dopamine content, such as the rat hypothalamus or primate substantia nigra [4].…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure is generally characterised by severe neurological disturbance and with Parkinson's like pathology (tremors, loss of coordination, motor skill deficits) whereas chronic exposure can result in milder motor skills deficits and mood disturbances (Bouchard et al, 2007;Bouchard et al, 2011;Bowler et al, 1999;Mergler et al, 1999;Roels et al, 2012). Manganese affects neurological development and the central nervous system by interfering with the function of the neurotransmitter dopamine (Aschner and Aschner, 1991;Butterworth et al, 1995;Normandin and Hazell, 2002;Verity, 1999). Manganese accumulates in the central nervous system resulting in increasing damage with long-term exposure (Rivera-Mancia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is associated with neurological and liver pathologies in adults (Butterworth et al, 1995;Laohaudomchok et al, 2011) The purpose of this research is twofold. Firstly to investigate historical exposure to manganese from a bioarchaeological and anthropological framework and secondly to establish baseline exposure data that may inform future investigations into manganese exposure in urban South Africans.…”
Section: Introductionmentioning
confidence: 99%